Thrombelastography during and after Elective Abdominal Surgery - Butler, J M (Thrombosis and Haemostasis, 1978)
Thrombelastography has been performed on recalcified whole blood from 50 patients before, during and after elective abdominal surgery. The characteristic changes of the thrombelastographic indices r, k and mA are described.During operation r and k shortened, but no change in mA was observed. This response was in part associated with an increase in factor VIII activity. Following operation, while r time was somewhat shortened, much more marked changes in k and mA were evident. Increasing fibrinogen concentration was the dominant factor in determining the post-operative changes in the thrombelastograph.